Capillary plexuses are vulnerable to neutrophil extracellular traps. Issue 2 (22nd January 2016) - Boneschansker, Leo; Inoue, Yoshitaka; Oklu, Rahmi; Irimia, Daniel
Abstract : We show that the trapping of neutrophil-derived chromatin fibres at the entrance of microchannel networks in vitro can result in the formation of disproportionately large areas with no RBC traffic. Abstract : Capillary plexuses are commonly regarded as reliable networks for blood flow and robust oxygen delivery to hypoxia sensitive tissues. They have high levels of redundancy to assure adequate blood supply when one or more of the capillaries in the network are blocked by a clot. However, despite having extensive capillary plexuses, many vital organs are often subject to secondary organ injury in patients with severe inflammation. Recent studies have suggested that neutrophils play a role in this pathology, even though their precise contribution remains elusive. Here we investigate the effect of chromatin fibres released from overly-activated neutrophils (neutrophil extracellular traps, NETs) on the flow of blood through microfluidic networks of channels replicating geometrical features of capillary plexuses. In an in vitro setting, we show that NETs can decouple the traffic of red blood cells from that of plasma in microfluidic networks. The effect is astonishingly disproportionate, with NETs from less than 200 neutrophils resulting in more than half of a 0.6 mm 2 microfluidic network to become void of red blood cell traffic. Importantly, the NETs are able to perturb the blood flow in capillary networks despite the presence of anti-coagulants. If verified to occur in vivo, this finding could represent a novel mechanism for tissue hypoxia and secondary organ injury during severe inflammation in patients already receiving antithrombotic and anticoagulant therapies.